Class III Peroxidases (POD) in Pepper (Capsicum annuum L.): Genome-Wide Identification and Regulation during Nitric Oxide (NO)-Influenced Fruit Ripening - Salvador González-Gordo; María A. Muñoz-Vargas; José M. Palma; Francisco J. Corpas (MDPI AG, 2023)
The class III peroxidases (PODs) catalyze the oxidation of several substrates coupled to the reduction of H2O2 to water, and play important roles in diverse plant processes. The POD family members have been well-studied in several plant species, but little information is available on sweet pepper fruit physiology. Based on the existing pepper genome, a total of 75 CaPOD genes have been identified, but only 10 genes were found in the fruit transcriptome (RNA-Seq). The time-course expression analysis of these genes showed that two were upregulated during fruit ripening, seven were downregulated, and one gene was unaffected. Furthermore, nitric oxide (NO) treatment triggered the upregulation of two CaPOD genes whereas the others were unaffected. Non-denaturing PAGE and in-gel activity staining allowed identifying four CaPOD isozymes (CaPOD I-CaPOD IV) which were differentially modulated during ripening and by NO. In vitro analyses of green fruit samples with peroxynitrite, NO donors, and reducing agents triggered about 100% inhibition of CaPOD IV. These data support the modulation of POD at gene and activity levels, which is in agreement with the nitro-oxidative metabolism of pepper fruit during ripening, and suggest that POD IV is a target for nitration and reducing events that lead to its inhibition.